Validity of the Czech Translation of the Adult Attention-Deficit/Hyperactivity Disorder (ADHD) Self-Report Scale (ASRS) - Vňuková, Martina; Ptáček, Radek; Děchtěrenko, Filip; Raboch, Jiří; Anders, Martin; Goetz, Michal (Frontiers in Psychology, 2022)
Abstract Objective The study aim was to assess the psychometric properties of the ASRS in the Czech Republic. Although this screening tool is now frequently used, its validity has not been assessed among the general Czech population. Methods The ASRS and WURS were administered online to the general Czech population (N = 1518). We performed confirmatory and exploratory factor analyses. Results For the ASRS, confirmatory factor analysis showed good fit for the screening part (SRMR = 0.03, RMSEA = 0.06, CFI = 0.98). For the symptom list, the fit was good according to the SRMR, acceptable according to the RMSEA and slightly below acceptable according to the CFI. For the WURS, the results showed SRMR = 0.06, RMSEA = 0.07, and CFI = 0.92. Conclusion The Czech translation of the ASRS is appropriate and has acceptable psychometric properties. However, we strongly recommend only using this tool together with clinical judgment.